The Cambridge international handbook of lean production diverging theories and new industries around the world - Janoski, Thomas; Lepadatu, Darina (Cambridge University Press, 2021)
This handbook focuses on two sides of the lean production debate that rarely interact. On the one hand, management and industrial engineering scholars have presented a positive view of lean production as the epitome of efficiency and quality. On the other hand, sociology, industrial relations, and labor relations scholars focus on work speedups, management by stress, trade union positions, and self-exploitation in lean teams. The editors of this volume understand the merits of both views and present them accordingly, bridging the gaps among five disciplines and presenting the best of each perspective. Chapters by internationally acclaimed authors examine the positive, negative and neutral possible effects of lean, providing a global view of lean production while adjusting lean to the cultural and political contexts of different nation-states. As the first multi-lens view of lean production from academic and consultant perspectives, this volume charts a way forward in the world of work and management in our global economy